2004
DOI: 10.1007/s00384-003-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of the NFKBIA gene is associated with Crohn's disease patients lacking a predisposing allele of the CARD15 gene

Abstract: The findings indicate that the phenotype Crohn's disease is to be substructured with respect to genetic susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 20 publications
2
53
1
Order By: Relevance
“…In studies with type 1 diabetes mellitus, AA genotype of rs696 was a risk factor for latent autoimmune diabetes in adults [17]. rs696 variation has also been associated with development of type 2 diabetes and Crohn's diseases, resulting in Th1/Th2 imbalance as the pathogenesis [16,37]. Recently, Hung et al [38] investigating IKBa -881A, -826T, -550A, -519T and -297C polymorphisms concluded that NFKBIA promoter gene polymorphisms (-826 C/T, -826 T/T genotypes) are higher in BD, but only -826 T/T genotype is associated with skin lesions in Taiwanese patients with BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies with type 1 diabetes mellitus, AA genotype of rs696 was a risk factor for latent autoimmune diabetes in adults [17]. rs696 variation has also been associated with development of type 2 diabetes and Crohn's diseases, resulting in Th1/Th2 imbalance as the pathogenesis [16,37]. Recently, Hung et al [38] investigating IKBa -881A, -826T, -550A, -519T and -297C polymorphisms concluded that NFKBIA promoter gene polymorphisms (-826 C/T, -826 T/T genotypes) are higher in BD, but only -826 T/T genotype is associated with skin lesions in Taiwanese patients with BD.…”
Section: Discussionmentioning
confidence: 99%
“…This gene probably plays an important role in inflammatory immunological diseases such as Crohn's disease or autoimmune diabetes mellitus [16,17]. According to Goto et al [18], the alterations in the expression of IjBa protein were related to the SNP rs696 in the 3 0 UTR region of the NFKBIA gene and led to a change in NF-jB activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many polymorphisms of the NFKBIA gene have been identified;recently, these polymorphisms have attracted widespread attention [13]. A number of case-control studies have been conducted to investigate the association of these polymorphisms with autoimmune and inflammatory diseases [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, these studies reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although polymorphisms within the IKBα gene have been described to be associated with MM, 24,25 Crohn's disease, 26 trachoma, 27 sarcoidosis, 28 and invasive pneumococcal disease, 29 the role of genetic variation within critical components of the NF-κB pathway, including NFKB2 and TRAF3, remains unexplored in myeloma. Moreover, whether polymorphisms in NF-κB pathwayrelated genes influence the efficacy of bortezomib-based treatment in MM patients is unknown.…”
Section: Introductionmentioning
confidence: 99%